India’s Collaboration with Australia in Science and Technology: A Scientometric Study of Co-Authored Papers During 1995-1999 - Gupta, B.M.; Dhawan, S.M.; Bose, P.R.; Mishra, P.K. (DESIDOC Journal of Library & Information Technology, 2003)
International collaborations are being viewed as an important instrument for the advancement of science throughout the world, particularly by the developing countries. India could well realise the significance of international collaboration in science and hence has, therefore, signed various S&T collaboration agreements with many developed and developing countries. With Australia also such collaboration is starting to take off at the government level, but at the institutional level it already exists. In this study the scientific collaboration between India and Australia has been studied on the basis of the number of joint publications brought out by Indian and Australian scientists, as reflected through co-authored papers during the period 1995-1999. The study reveals the extent, mode, and direction of collaborative research between the two nations. It also has been attempted to crystallise and identify the priority S&T areas for collaborative research between the two countries. The impact of such collaborative research has been studied through the analysis of impact factor of publications where this joint research is published. It has been revealed that the average value of impact factor per paper for multilateral papers is far above the average impact factor of all papers. It is also found that in about 38% of the India-Australian collaborated papers the other countries were also involved, which included the USA, the UK, Russia, New Zealand, France, Switzerland, and even Italy, Japan and China. The study revealed the present status of collaboration between Australia and India in S&T, and such a study can help the policy makers to identify and explore the future areas of collaboration between the two countries. http://dx.doi.org/10.14429/dbit.22.6.3580